2008
DOI: 10.1007/s10802-008-9251-7
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Class Norm: Bullying Behavior of Popular Adolescents and its Relation to Peer Acceptance and Rejection

Abstract: This study examined to what extent bullying behavior of popular adolescents is responsible for whether bullying is more or less likely to be accepted or rejected by peers (popularity-norm effect) rather than the behavior of all peers (class norm). Specifically, the mean level of bullying by the whole class (class norm) was split into behavior of popular adolescents (popularity-norm) and behavior of non-popular adolescents (non-popularitynorm), and examined in its interaction with individual bullying on peer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
197
2
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(224 citation statements)
references
References 47 publications
9
197
2
13
Order By: Relevance
“…These and other (compositional) characteristics of the peer context may affect the processes by which behavioral similarity comes about. For example, it may be that instead of classmates in general, the strongest influence on individual health-risk behavior comes from classmates with whom the adolescent shares a dyadic relationship or classmates with a high social reputation in the classroom (e.g., Dijkstra, Lindenberg, & Veenstra, 2008).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…These and other (compositional) characteristics of the peer context may affect the processes by which behavioral similarity comes about. For example, it may be that instead of classmates in general, the strongest influence on individual health-risk behavior comes from classmates with whom the adolescent shares a dyadic relationship or classmates with a high social reputation in the classroom (e.g., Dijkstra, Lindenberg, & Veenstra, 2008).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…By almost exclusively attributing the causes of bullying to the bully or the victim, teenagers risk overlooking other factors that might cause or influence the process of peer harassment. Bullying prevention efforts and interventions have to help children and adolescents to discover, understand and consider the complexity of bullying and factors such as social participation roles in bullying and the power and responsibility of bystanders (O'Connell et al 1999;Salmivalli 2010;Salmivalli et al 1996), the everyday process of making and maintaining friendships by defining and excluding nonfriends (Besag 2006;Mishna et al 2008;Owens et al 2000;Thornberg in press), instability in peer networks (Besag 2006;Neal 2007), the power of group norm settings by popular classmates (Dijkstra et al 2008), social hierarchy (Frisén et al 2008;Kless 1992;Neal 2007;Thornberg in press), probullying norms (Duffy and Nesdale 2009;Salmivalli and Voeten 2004), group processes and group pressure (Bukowski and Sippola 2001;Burns et al 2008;Hamarus and Kaikkonen 2008), social representations or peer discourses about victims and bullying (Teräsahjo and Salmivalli 2003;Thornberg 2010b), gender (Kless 1992;Neal 2007;Phoenix et al 2003;Stoudt 2006), heterosexual hegemony (Phoenix et al 2003;Ringrose 2008), and intolerance of diversity (MacDonald and Swart 2004;Merton 1994;Thornberg in press) in peer culture. Hence, it appears to be urgent to deepen children's and young people's insights into peer attributing, school attributing, and human nature/society attributing, since these are atypical bullying explanations among the young people in our current findings.…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…In other words, if adolescents perceive that their peers value aggressive behavior, they may intentionally use it to gain social status, constituting a mechanism for social adaptation. Whereas, in the realm of bullying, several studies have shown that bullying may serve as a way of positioning individuals in the peer social hierarchy (Dijkstra et al 2008;Olthof & Goosens, 2007;Rodkin & Berger, 2008). Bullies can be popular and socially central in their social groups (Rodkin et al, 2006).…”
Section: Aggression Bullying and Social Statusmentioning
confidence: 99%
“…Another study found that the negative association between bullying and peer acceptance faded when bullies where high in machiavellianism (Wei & Chen, 2012). Seemingly, Dijkstra et al (2008) found that the associations between bullying and peer rejection (positive) and peer acceptance (negative) were weakened when the perpetrator of bullying behavior was highly popular. These differences may be due to attributional biases and also to peer beliefs regarding these behaviors (Lansu et al 2013;van Goethem et al, 2010).…”
Section: Distinguishing Aggression and Bullying As Status Correlatesmentioning
confidence: 99%